The effectiveness of electronic student worksheet based on Process Oriented Guided Inquiry Learning (POGIL) - Hidayat, Taufik; Kurmalasari, Tety; Zaitun; Abdulhajar, Encik (Educenter : Jurnal Ilmiah Pendidikan, 2025)
This study aims to determine the effectiveness of an electronic student worksheet based on the Process Oriented Guided Inquiry Learning model in improving students learning outcomes on chemical calculation material at an Islamic senior high school. The research applied a quasi experimental approach using a one group design. The participants were students from a science class who learned through an electronic worksheet developed according to the stages of orientation exploration concept invention and application. The learning process emphasized active inquiry collaboration and guided knowledge construction supported by digital media. Data on student learning outcomes were collected through achievement tests. The results indicate a meaningful improvement in students learning outcomes after using the electronic worksheet. This finding shows that the POGIL based electronic worksheet has a strong influence on enhancing students conceptual understanding and problem solving skills. In addition the electronic worksheet facilitates active and collaborative learning while integrating technology into chemistry instruction. The learning materials also incorporate Qur’anic values that support character building alongside scientific understanding. Overall the findings confirm that electronic student worksheets based on Process Oriented Guided Inquiry Learning are effective instructional tools for improving chemistry learning outcomes and supporting holistic student development in digital learning environments.